2015
DOI: 10.1021/acs.orglett.5b00395
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Iodoazidation of Alkynes: Synthesis of α,α-Diazidoketones

Abstract: Aryl alkyl alkynes reacted with N-iodosuccinimide (NIS) and trimethylsilyl azide (TMSN3), leading to α,α-diazidoketones via the regioselective addition of IN3 to alkynes. Huisgen cyclization of α,α-diazidoketones generated bis-triazole compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…The (E)‐isomer was also observed in small amounts for 1 s – u . Interestingly, internal alkynes are required for reactivity, which is in line with the iodoazidation reaction reported earlier …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (E)‐isomer was also observed in small amounts for 1 s – u . Interestingly, internal alkynes are required for reactivity, which is in line with the iodoazidation reaction reported earlier …”
Section: Methodsmentioning
confidence: 99%
“…No formation of the corresponding chloroazidoalkenes was observed when replacing the benzoate group with H ( 1 v ), OH ( 1 w ), OTBS ( 1 x ) or OAc ( 1 y ) substituents, and this, along with the unique regioselectivity of the final product, implied neighboring group participation of the benzoate group in the reaction pathway. Yanada and co‐workers demonstrated isomerization of the C=C double bond during the iodoazidation process of alkynes, after the isolated mixture of E and Z isomers was exposed to the same reaction conditions . However, using our standard reaction conditions, no isomerization of the double bond of isolated ( E )‐ 2 c took place after stirring for 12 h. The formation of the corresponding chloroazidoalkenes of dialkyl ( 1 p–s ) substrates excludes the existence of allene intermediates.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015 a direct diazidation with iodine and sodium azide at room temperature was published by Kirsch et al [6]. Yanada suggest a way for synthesis of α,α-diazoketones using N-iodosuccinimide (NIS) and trimethylsilyl azide (TMSN 3 ) [7]. Although a great overview over synthesis and chemistry of organic diazides is given by Häring and Kirsch [8] and azido ester plasticizers have still great attention [9] the geminal diazidation of already azidized compounds wasn't described before.…”
Section: Introductionmentioning
confidence: 99%
“…A general methodology is still lacking for the complete reductive azido‐functionalization of triple bond of alkynes to provide functionalized alkanes. Pioneering work in this context, Yanada et al have reported the synthesis of diazidoketones (geminal diazides) by reaction of aryl alkyl alkynes, N ‐iodosuccinimide (NIS) and TMSN 3 (Scheme a). However, lack of wide substrate scope limits their application.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey showed that the reactivities of geminal diazides have not been much established though only a few members of which have been known. [9,12] Apart from these reports, their utilization for heterocycles synthesis is not much explored. [13] In this context, we have also demonstrated the versatility of geminal diazides via a first cycloaminative approach towards quinoxalines and synthesis of bis-triazole derivatives under copper catalysis.…”
mentioning
confidence: 99%